Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3233/jad-215719
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of α-Klotho Are Correlated with Cerebrospinal Fluid Levels and Predict Measures of Cognitive Function

Abstract: Background: α-klotho might play a role in neurodegenerative diseases. Objective: To determine levels of α-klotho and apoE in serum and cerebrospinal fluid (CSF) samples and their relationship with the Mini-Mental State Examination (MMSE) and Clinical Dementia Rating (CDR). Methods: All subjects were between age 39 to 83+ (n = 94). CDR and MMSE were administered to all participants. CSF was collected in the early afternoon by lumbar puncture. Results: Serum and CSF levels of α-klotho are positively correlated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 43 publications
(49 reference statements)
1
15
0
1
Order By: Relevance
“…It has been thought that Klotho levels in the blood and CSF are independent. Contrary to that view, some investigators have recently reported that serum and CSF levels correlate strongly, and high levels predict better cognitive function ( Kundu et al, 2022 ). This is of major interest for future clinical studies, especially concerning drugs or other treatments that increase Klotho.…”
Section: Klotho and Neurodegenerative Diseasesmentioning
confidence: 97%
See 2 more Smart Citations
“…It has been thought that Klotho levels in the blood and CSF are independent. Contrary to that view, some investigators have recently reported that serum and CSF levels correlate strongly, and high levels predict better cognitive function ( Kundu et al, 2022 ). This is of major interest for future clinical studies, especially concerning drugs or other treatments that increase Klotho.…”
Section: Klotho and Neurodegenerative Diseasesmentioning
confidence: 97%
“…In the 55–85 age group, however, levels were more consistently low. CSF levels are also quite variable ( Kundu et al, 2022 ). In view of this, results obtained from small groups should be interpreted with caution.…”
Section: Klotho and Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The serum and cerebrospinal fluid levels of α-KL are positively correlated with and predict scores on the Mini-Mental State Examination and Clinical Dementia Rating, regardless of sex (16). Additionally, a study related to the most common neurodegenerative disease (i.e., Alzheimer's disease) has shown that the disease leads to decreased α-KL expression in the brain, and the overexpression of α-KL improves cognitive function by inhibiting neuroinflammation, promoting amyloid β-protein (Aβ) clearance, and mitigating Tau pathology (17).…”
Section: Introductionmentioning
confidence: 94%
“…High α-klotho levels were shown to especially benefit apoE4 carriers [ 8 , 16 ]. However, in people between 39 and 90 years of age, serum and CSF levels of α-klotho are positively correlated and predict scores on both the Mini-Mental State Examination test and the Clinical Dementia Rating regardless of sex or APOE genotype [ 168 ]. There is a robust positive relationship between α-klotho and apoE levels in the amygdala in irradiated non-human primates [ 18 ].…”
Section: Contributions Of the Periphery To Cns Insulin Actionsmentioning
confidence: 99%